1ISG-004 Impact of a lean approach on the organisation of a chemotherapy production unit. (2nd March 2018) - Carrez, L; Martin, V; Jermini, M; Malet, V; Bouchoud, L; Falaschi, L; Bonnabry, P
Abstract : Background: Our chemotherapy production unit decided to rethink its organisational strategy and to revise its production processes through lean methodology to meet growing activity, in the context budget constraints that limit the increase in staff. Purpose: To evaluate the impact of a lean management approach on the efficiency of a chemotherapy unit. Material and methods: A five-step lean methodology approach was applied with a team of 12 technicians and five pharmacists supported by a lean expert, from January 2015 to July 2016: DEFINE: objectives, value stream mapping, process flows. MEASURE: steps, process duration, use of stock. ANALYSE: added-value steps, waste, waiting time and causes. IMPLEMENT: imagine and implement solutions. CONTROL: efficiency, performance, satisfaction. Results: The team identified 73 items impacting the efficiency of the process during the 'Measure' phase. During the 'Analyse' step, 18 opportunities divided into four main themes were proposed to improve the organisation: Flow: smoothing the activity and reducing the early morning peak (–12% between 7 and 9 am), producing continuously according to demand of the day ('Just in time' eight maximum ongoing preparations), improving occupancy rates of isolators (+25% between 10 and 12 am, and +20% between 1 and 4 pm), revising the steps of double–control and using mistake–proofing resulted in a decrease in crossing time of manufacturing from 9 hour 45 min to 1 hour 45 min. bull; Space: reorganisation with a reduction of unnecessary movements. bull; Management: creation of a position of 'coordinator of the day', and daily meetings ('Obeya') to reassign tasks. bull; Stock and control: rationalisation of storage and orders. A net gain of 40% full-time equivalent was reached. The satisfaction survey showed a positive acceptance of the project and its conduct. Conclusion: The application of a lean methodology allowed the optimisation of the management of our chemotherapy production unit and saved human resources. The main actions were to eliminate waiting time, to smooth daily activity, and to reorganise roles, spatial organisation and storage. The positive impact on the efficiency of our facility and the satisfaction of the team proved that lean methodology is a relevant tool in the hospital pharmacy. No conflict of interest